2009
DOI: 10.1177/0193945909334433
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an Internet Physical Activity Intervention

Abstract: The Internet is a relatively new method of delivering strategies for health behavior change. The purpose of this study was to determine the feasibility of delivering a physical activity intervention by the Internet to improve outcomes in adults with the metabolic syndrome. Twenty-two participants (16 males; 6 females) were recruited from a cardiology clinic database, age range 32-66 years. Participants were randomly assigned to the Internet intervention (n = 12) or the usual care ( n = 10) group. The mean tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…The study by Bosak et al showed that web-based intervention to increase physical activity in people with metabolic syndrome appears feasible [22]. Recent evidence support that lifestyle interventions including physical activity and low-calorie diet might lead to at least 10% weight loss [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Bosak et al showed that web-based intervention to increase physical activity in people with metabolic syndrome appears feasible [22]. Recent evidence support that lifestyle interventions including physical activity and low-calorie diet might lead to at least 10% weight loss [88].…”
Section: Discussionmentioning
confidence: 99%
“…A web-based intervention provides easily access to evidence-based content in every time and makes it feasible to increase tremendously the number of people reached to information [20, 22, 23]. According to Barak et al a web-based intervention is: ‘a primarily self-guided intervention program that is executed by means of a prescriptive online program operated through a website and used by consumers seeking health- and mental-health related assistance’ [24].…”
Section: Introductionmentioning
confidence: 99%
“…These types of interventions would be meaningful for users with time and geographic restrictions 1,17-19 because they make it possible for researchers to reach a large number of participants without any time and geographical limitations. 20,21 In addition, Webbased interventions are meaningful for people with mobility and speech limitations, allowing them easy access to the …”
Section: Meaningfulness and Effectivenessmentioning
confidence: 99%
“…[23][24][25][26][27][28] Moreover, Web-based interventions provide flexibility for users to control content, time, location, speed, and learning schedule. 21,[29][30][31] They allow the researchers to easily update and modify the content of the interventions 32,33 and to use various multimedia functions (eg, sound, image, and animations) in order to attract potential participants. 18,19 Subsequently, some studies reported the effectiveness of Web-based interventions in facilitating users' learning experience, 21,29-31 which could be another meaningful use of the interventions.…”
Section: Critical Questions To Ask In Development Of Web-based Intervmentioning
confidence: 99%
See 1 more Smart Citation